Metal-catalyzed transformations of cyclopropanols via homoenolates - Sekiguchi, Yoshiya (2022)
Metal homoenolates represent uniquely useful organometallic intermediates in synthetic chemistry, allowing umpolung synthesis of β-functionalized carbonyl compounds. While siloxycyclopropanes had been established as reliable precursors to homoenolates, often stoichiometric, for diverse carboncarbon bond forming reactions, unprotected cyclopropanols have emerged as alternative and attractive precursors to homoenolates, often catalytically generated, in carboncarbon and carbonheteroatom bond-forming reactions. This review article provides an overview of the development of such homoenolate transformations, as classified with respect to the metals involved in the cyclopropane ring opening.